Effect of Cold Plasma on Cell Viability and Collagen Synthesis in Cultured Murine Fibroblasts - 石兴民 蔡晶芬 许桂敏 任鸿斌 陈思乐 常正实 刘进仁 黄崇亚 张冠军 吴喜利 (Plasma science & technology, 2016)
An argon atmospheric pressure plasma jet was employed to treat L929 murine fibroblasts cultured in vitro.Experimental results showed that,compared with the control cells,the treatment of fibroblasts with 15 s of plasma led to a significant increase of cell viability and collagen synthesis,while the treatment of 25 s plasma resulted in a remarkable decrease.Exploration of related mechanisms suggested that cold plasma could up-regulate Cyclin D1 gene expression and down-regulate p27 gene expression at a low dose,while it could down-regulate Cyclin D1 expression and up-regulate p27 expression at a higher dose,thus altering the cell cycle progression,and then affecting cell viability and collagen synthesis of fibroblasts.